2020
DOI: 10.1002/btpr.2964
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and structural insights into the high substrate affinity of a dimeric and Ca2+ independent Bacillus subtilis α‐amylase

Abstract: An extracellular amylase (AmyKS) produced by a newly isolated Bacillus subtilis strain US572 was purified and characterized. AmyKS showed maximal activity at pH 6 and 60°C with a half‐life of 10 min at 70°C. It is a Ca2+ independent enzyme and able to hydrolyze soluble starch into oligosaccharides consisting mainly of maltose and maltotriose. When compared to the studied α‐amylases, AmyKS presents a high affinity toward soluble starch with a Km value of 0.252 mg ml−1. Coupled with the size‐exclusion chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…BvAmylase exhibited the optimal activity at pH 6.0, and it was active at a narrow range of pH, displaying 86.63% and 69.05% activity at pH 5.0 and pH 7.0, respectively. These results were similar to AmyKS from Bacillus subtilis strain US572 with optimal pH 6.0 and showing 65.00% and 76.00% activity at pH 5.0 and pH 7.0, respectively [26]. Hence, this enzyme is suitable to be used in acidic conditions in industries.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…BvAmylase exhibited the optimal activity at pH 6.0, and it was active at a narrow range of pH, displaying 86.63% and 69.05% activity at pH 5.0 and pH 7.0, respectively. These results were similar to AmyKS from Bacillus subtilis strain US572 with optimal pH 6.0 and showing 65.00% and 76.00% activity at pH 5.0 and pH 7.0, respectively [26]. Hence, this enzyme is suitable to be used in acidic conditions in industries.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, SDS-PAGE result showed that the relative molecular weight of BvAmylase was approximately 72.0 kDa, which was similar to the α-amylase AmyJ33 (72.0 kDa) from Bacillus amyloliquefaciens JJC33M [22] and the α-amylase AmyBS-1 (72.3 kDa) in Bacillus subtilis AS01a [23], was higher than the α-amylase FMB1 (58.5 kDa) in Anoxybacillus ayderensis [5], the α-amylase (52.0 kDa) in Bacillus amyloliquefaciens [24], the α-amylase (56.0 kDa) in Bacillus sp. YX-1 [25] and the α-amylase AMY1 (47.0 kDa) in Massilia timonae [6], however, was lower than the α-amylase AmyKS (136.9 kDa) in Bacillus subtilis strain US572 [26] and the α-amylase (85.0 kDa) in Bacillus licheniformis AT70 [27].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Accordingly, a-amylases account for 25% of the world's multi-billion dollar enzyme market. 1,2 a-Amylases are endo-acting enzymes that cleave starch into malto-oligosaccharides, which are further degraded by exoacting a-glucosidases, glucoamylases, b-amylases and a-glucan phosphorylases and lyases. They are found in CAZy GH families 13, 57, 119 and 126, with the vast majority in the large GH13 family.…”
mentioning
confidence: 99%
“…The active enzyme concentration can be quantied from such plots by extrapolating the steady-state portion back to the y-intercept (t ¼ 0) and tting the burst to eqn (1), as described previously. 11 Burst ¼ [E] 0 Â (k on /k on + k off ) 2 (1)…”
mentioning
confidence: 99%